Sex‐related effects in major depressive disorder: Results of the European Group for the Study of Resistant Depression. Issue 9 (10th June 2021) - Bartova, Lucie; Dold, Markus; Fugger, Gernot; Kautzky, Alexander; Mitschek, Marleen M. M.; Weidenauer, Ana; Hienert, Marius G.; Frey, Richard; Mandelli, Laura; Zohar, Joseph; Mendlewicz, Julien; Souery, Daniel; et al.
Abstract: Background: Sex‐related effects on the evolution and phenotype of major depressive disorder (MDD) were reported previously. Methods: This European multicenter cross‐sectional study compared sociodemographic, clinical, and treatment patterns between males and females in a real‐world sample of 1410 in‐ and outpatients with current MDD. Results: Male MDD patients (33.1%) were rather inpatients, suffered from moderate to high suicidality levels, received noradrenergic and specific serotonergic antidepressants (ADs) as first‐line AD treatment, generally higher mean AD daily doses, and showed a trend towards a more frequent administration of add‐on treatments. Female MDD patients (66.9%) were rather outpatients, experienced lower suicidality levels, comorbid thyroid dysfunction, migraine, asthma, and a trend towards earlier disease onset. Conclusions: The identified divergencies may contribute to the concept of male and female depressive syndromes and serve as predictors of disease severity and course, as they reflect phenomena that were repeatedly related to treatment‐resistant depression (TRD). Especially the greater necessity of inpatient treatment and more complex psychopharmacotherapy in men may reflect increased therapeutic efforts undertaken to treat suicidality and to avoid TRD. Hence, considering sex may guide the diagnostic and treatment processes towards targeting challenging clinical manifestations including comorbidities and suicidality, and prevention of TRD and chronicity.